MALT Lymphoma Presenting with Peripheral Ulcerative Keratitis - Patil S; Colby K; Lazzaro D (International Medical Case Reports Journal, 2022)
Sachi Patil, Kathryn Colby, Douglas Lazzaro Department of Ophthalmology, New York University Langone Health, New York, NY, USACorrespondence: Sachi Patil, New York University Grossman School of Medicine, 550 First Avenue, New York, NY, 10016, USA, Tel +1 (631)-793-2594, Email sachi.patil@nyulangone.orgObjective: To report a case of ocular mucosa-associated lymphoid tissue (MALT) lymphoma presenting with peripheral ulcerative keratitis.Methods: A 58-year-old man with a history of vitreous syneresis in both eyes and glaucoma presented with an abnormal, painful sensation of the left eye and mild hyperemia. Physical examination revealed peripheral ulcerative keratitis superiorly and a salmon-colored lesion in the superior conjunctiva.Results: The differential diagnosis of superior corneal thinning includes collagen vascular disease, Terrien’s marginal degeneration, infectious keratitis, and other forms of peripheral keratitis. Our patient was diagnosed with conjunctival MALT lymphoma by surgical excision of the mass, and the peripheral ulcerative keratitis may be related to this diagnosis.Conclusion: Although rare, this case demonstrates a peripheral keratitis possibly related to the underlying disease of MALT lymphoma. The patient is being treated with local radiation treatment.Keywords: ocular lymphoma, peripheral ulcerative keratitis, MALT lymphoma